2019
DOI: 10.1007/s10701-019-00251-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaporating Black-Holes, Wormholes, and Vacuum Polarisation: Must they Always Conserve Charge?

Abstract: A careful examination of the fundamentals of electromagnetic theory shows that due to the underlying mathematical assumptions required for Stokes' Theorem, global charge conservation cannot be guaranteed in topologically non-trivial spacetimes. However, in order to break the charge conservation mechanism we must also allow the electromagnetic excitation fields D, H to possess a gauge freedom, just as the electromagnetic scalar and vector potentials ϕ and A do. This has implications for the treatment of electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This means that there are cases where it is advantageousor even required -to write the axionic response in our way. These results are linked to related discoveries [4] enabled by removing (D, H), such as non-conservation of charge in topologically non-trivial spaces, and the treatment of charges passing through wormholes. We also remarked on the possibility of there being an additional 16 more exotic constitutive parameters, for a grand total of 55 in all.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This means that there are cases where it is advantageousor even required -to write the axionic response in our way. These results are linked to related discoveries [4] enabled by removing (D, H), such as non-conservation of charge in topologically non-trivial spaces, and the treatment of charges passing through wormholes. We also remarked on the possibility of there being an additional 16 more exotic constitutive parameters, for a grand total of 55 in all.…”
Section: Discussionmentioning
confidence: 77%
“…But for a non-dispersive medium, as we consider here, the tensors (κ DE ,κ DB ,κ HE , κ HB ) have no additional dependence. The nature of the excitation fields (D, H) is very different to the electromagnetic fields (E, B), and indeed there is a debate in the literature as to whether or not they are actually physical quantities [3,4,29]. Notably, it is easy to see that Maxwell's equations are invariant by adding a gauge (φ g , A g ) to the excitation fields, with the replacements…”
Section: Maxwell's Equations and The Constitutive Tensormentioning
confidence: 99%
See 1 more Smart Citation
“…Here we consider a 2D radial morphism where points with a laboratory or device coordinater are transformed so as to appear at some apparent or design position = (ˆ) r f r , just as in the T-Design for a cylindrical cloak. Within this general approach, we can describe not only cloaks but also various types of illusion and/or distortion devices, and even two universes connected by a wormhole [29] 3 . However, we keep the mathematics general so that other non-cloak morphisms are allowed by the theory presented here.…”
Section: Radial Transformation Designsmentioning
confidence: 99%
“…The role and meaning of the Maxwell excitation fields (D D D, H H H) has been a subject of debate, with arguments for and against their independent existence and measurability [1][2][3][4][5][6]. However, a recent work has demonstrated that in certain physical circumstances, such as when a black hole forms then evaporates, (D D D, H H H) cannot be guaranteed to be uniquely defined [7]. This reduces (D D D, H H H) into the role of a gauge field for the current, meaning that there is no role for attempting to measure them.…”
Section: Introductionmentioning
confidence: 99%